MANFAAT TRANSPORTASI KAPAL FERI UNTUK PERTUMBUHAN EKONOMI PADA KAWASAN PULAU TERLUAR, DAN EFEK PEMBERIAN SUBSIDI DARI PEMERINTAH - Syaputra, Prasetya Ega; Dianto, Mas Akbar Suhar; Saputra, Hilman (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research discusses the benefits of ferry transportation for economic growth in outer island areas and the impact of providing government subsidies. Outer islands often experience accessibility problems, which can limit economic growth and community welfare. Ferry transport was identified as an effective solution to overcome this challenge. The research uses literature study methods and economic data analysis with a focus on the outermost islands in the Riau Islands Province, Indonesia. The research results show that ferry transportation not only facilitates inter-island connectivity, but also becomes a catalyst for economic growth, especially in the tourism and trade sectors. Providing government subsidies for ferry services has a positive impact, maintaining operational sustainability and reducing the cost burden on local residents.